Discovery of Antiamebic Compounds That Inhibit Cysteine Synthase From the Enteric Parasitic Protist Entamoeba histolytica by Screening of Microbial Secondary Metabolites - Mori, Mihoko; Tsuge, Satoshi; Fukasawa, Wataru; Jeelani, Ghulam; Nakada-Tsukui, Kumiko; Nonaka, Kenichi; Matsumoto, Atsuko; Ōmura, Satoshi; Nozaki, Tomoyoshi; Shiomi, Kazuro (Frontiers in Cellular and Infection Microbiology, 2018)
Amebiasis is caused by infection with the parasite, Entamoeba histolytica. Although metronidazole has been used against amebiasis, it shows side effects and low efficacy against asymptomatic cyst carriers. Therefore, drugs with new mode of action or targets are urgently needed. L-cysteine is the major thiol and an essential amino acid for proliferation and anti-oxidative defense of E. histolytica. E. histolytica possesses the de novo L-cysteine biosynthetic pathway, consisting of two reactions catalyzed by serine acetyltransferase and cysteine synthase (CS). As the pathway is missing in humans, it is considered to be a rational drug target against amebiasis. In this study, we established the new screening system to discover antiamebic compounds that target the de novo cysteine biosynthesis. The screening allowed us to identify the compounds that differentially affect the growth of the trophozoites in the cysteine-deprived media compared to the cysteine-containing medium. A total of 431 compounds of the Kitasato Natural Products Library and 6,900 of microbial culture broth extracts were screened. Five compounds, aspochalasin B, chaetoglobosin A, prochaetoglobosin III, cerulenin, and deoxyfrenolicin, from the Kitasato Natural Products Library, showed differential antiamebic activities in cysteine-deprived medium when compared to the growth in the cysteine-containing medium. The selectivity of three cytochalasans apparently depends on their structural unstability. Eleven microbial extracts showed selective antiamebic activities, and one fungal secondary metabolite, pencolide, was isolated. Pencolide showed cysteine deprivation-dependent antiamebic activity, although the IC50 value in the cysteine-deprived medium was rather high (283 M). Pencolide also showed inhibitory activity against EhCSs with comparable IC50 values. These results indicated that antiamebic activity of pencolide is attributable to inhibition of CS. Cytotoxicity of pencolide was 6.7 times weaker against mammalian MRC-5 cell line than E. histotytica. Pencolide has the maleimide structure, which is attacked by Michael donors including the thiol moiety of cysteine. The cysteine-adducts were detected by mass spectrometric analysis as predicted. Thus, we cannot exclude a possibility that the cysteine-adducts of pencolide may contribute cysteine-dependent toxicity of pencolide to the parasite. Taken together, pencolide is the first compound that inhibits CS and amebic cell growth in a cysteine-dependent manner with relatively low mammalian cytotoxicity.